Effectiveness of mobile applications for behavioral changes in health: a systematic review - Thais Rodrigues Paula; Angélica Paixão de Menezes; Nirla Gomes Guedes; Viviane Martins da Silva; Maria Vera Lúcia Moreira Leitão Cardoso; Erivando de Sena Ramos (Universidade Federal do Ceará, 2020)
Objective: to evaluate the effectiveness of mobile applications for behavioral changes focused in health. Methods: systematic review, from the PubMed, SCOPUS, Cochrane, PsycINFO, CINAHL, and Medline. The descriptors used were: Mobile applications and Health. The study used the protocol Preferred Reporting Items for Systematic reviews and Meta-Analyses, and the methodological quality was evaluated using the Joanna Briggs Institute® instrument. The final sample was made up of eight articles. Results: most randomized clinical trials showed that interventions with applications are potentially effective strategies to change behavior in health, especially when associated to other strategies in accordance to the specific population/context. The articles included in the review were in accordance to at least nine of the thirteen questions of methodological quality evaluation. Conclusion: the use of applications has impacts on behavioral change and contributes for positive results in the state of health.